Structural, magnetic and dielectric properties of FeTe1-xMx (M = Se, S) superconductor prepared by solid state reaction at ambient pressure - Lim, Edmund Hua Hang (2015)
The polycrystalline samples with nominal composition FeTe1-xSex (x = 0.1 - 0.5) and FeTe1-xSx (x = 0.1 - 0.3) were prepared via solid-state reaction method. The pellets were sealed inside a stainless steel tube with both ends clamped for sintering at ambient pressure. Argon gas flow was maintained throughout the heat treatment in order to minimize the oxidation. According to the X-ray diffraction (XRD) data, both FeTe1- xSex and FeTe1-xSx were indexed to tetragonal structure with space group of P4/nmm. The lattice parameters a- and c-axis decrease with the substitution of Se and S. SEM images showed that the samples developed into plate-like grain structure gradually with the increase of Se and S concentration. EDX results show that the ratio of Te substituted by Se and S are gradually increased with increasing of the Se and S concentration. For FeTe1-xSex, onset of superconducting transition temperature, Tc was found to increase with Se concentration. The Tc is about 13.8 K and 13.5 K for x = 0.4 and 0.5,respectively compared with 10.6 K for x = 0.1. Substitution of Te with S suppresses the antiferromagnetic transition of the parent compound FeTe as shown by the temperature dependence of magnetic moment measurements. The samples with S content x = 0.25 and 0.30 exhibited diamagnetism suggesting the coexistence of magnetic and superconducting phase in these samples. Both FeTe1-xSex and FeTe1-xSx exhibited ferromagnetic behaviour as shown by the field dependent magnetization. In general, the values of coercivity, retentivity and magnetization (at 10 kG) decrease with Se and S concentration. The values of these magnetic properties are comparable for both Se and S substitution. Both FeTe1-xSex and FeTe1-xSx show negative dielectric permittivity (εr′) and this could be due to the plasma-like behaviour of the electron gas at frequency less than the plasma frequency. Se substitution decreases the dielectric constants εr′, while increased the εr′′ from x = 0.0 to x = 0.5. For S substitution, εr′ decreased while εr′′ increase from x = 0.0 to x = 0.1. However, εr′ increased and εr′′ decreased with increasing S concentration for x = 0.25 and 0.30. FeTe1-xSx (x = 0.1) has greater magnitude of εr′ and εr′′, more rapid energy loss and higher ac-conductivity (ζac) compared to FeTe1-xSex (x = 0.1 - 0.3) at 1 kHz.